Resident Macrophages and Lymphocytes in the Canine Endometrium. Issue 5 (31st July 2015) - Pires, MA; Payan‐Carreira, R
Content: Resident immune cells play a major role in endometrial immunity and in tissue homoeostasis. This study aimed to analyse the distribution of macrophages, B and T lymphocytes (respectively, Mø, B‐Lym and T‐Lym) in the canine endometrium throughout the oestrous cycle and in late involution (at the proestrus stage post‐parturition). An immunohistochemistry technique was used on samples from 50 post‐pubertal healthy female dogs, of which five in late post‐partum. The distribution of resident immune cells was analysed in three endometrial layers (superficial, intermediate and basal areas). Mø, B‐Lym and T‐Lym were demonstrated to reside in the endometrium in all the stages of the canine cycle; their numbers being considerably higher during late involution. T‐Lym were scattered in the stroma or amidst the glandular epithelium, constituting the predominant immune cell population in anestrus and proestrus, but decreased in number at all other stages. Endometrial B‐Lym remained fairly constant during the canine cycle, although its numbers were higher in late involution. Mø counts were higher during anestrus compared to the other stages, the cells being displaced into the superficial endometrial layer. Mø demonstrated the highest level in late involution samples, forming small aggregates below the surface epithelium. The number of immune cells was not normally distributed, suggesting the influence of individual factors, such as age or parity, not explored herein due to limited sample availability. Still, this study provides important information for the interpretation of endometrial biopsies in dogs and for the understanding of the increased susceptibility to uterine infection during dioestrus found in the bitch.